Analisis Kemampuan Penalaran Matematis Siswa SMP Materi Geometri Ditinjau Gaya Kognitif Dan Tingkat Berfikir Geometri Van Hiele - Setiyawan, Ahmad Heri; Fauziyah, Nur; Fadholi, Ahmad (Postulat : Jurnal Inovasi Pendidikan Matematika, 2024)
Abstract Studying geometry can develop the ability to reason or think logically to solve problems related to shape statements, size, relative position of images, and the nature of space. Mathematical reasoning is students' thinking power in concluding and is the highest mathematical cognitive domain. Middle school-level students need help in mathematical reasoning at the conclusion-drawing stage. Qualitative descriptive research to describe the mathematical reasoning abilities of junior high school students. The research subjects for class VIII A UPT SMP Negeri 22 Gresik consisted of three field-dependent cognitive style students and three field-independent cognitive style students. Analysis of research data from the results of written tests and interviews with mathematical reasoning instruments on congruence and similarity of flat shapes and the Van Hiele Geometry Test. The results of research on the relationship between stages of geometric thinking levels and indicators of mathematical reasoning ability of two level 1 students, visualization meets three indicators; two analysis level 2 students met three indicators; and two level 3 students of informal deduction abstraction met five indicators. The average mathematical reasoning ability of the five indicators only provides reasons for several solutions and cannot check the validity of an argument and draw appropriate conclusions. Abstrak Mempelajari geometri dapat menumbuh kembangkan kemampuan dalam bernalar atau berpikir logis memecahkan masalah berkaitan dengan pernyataan bentuk, ukuran posisi relatif gambar, dan sifat ruang. Penalaran matematis adalah daya pikir siswa dalam menarik kesimpulan sesuatu dan ranah kognitif matematis paling tinggi. Siswa tingkat Sekolah Menengah Pertama kesulitan dalam penalaran matematis pada tahapan penarikan kesimpulan. Penelitian deskriptif kualitatif dengan tujuan mendeskripsikan kemampuan penalaran matematis siswa Sekolah Menengah Pertama. Subjek penelitian kelas VIII A UPT SMP Negeri 22 Gresik terdiri dari tiga siswa gaya kognitif Field Dependent dan tiga siswa gaya kognitif Field Independent. Analisis data peneliti dari hasil tes tertulis dan wawancara instrumen penalaran matematis kekongruenan dan kesebangunan bangun datar dan Van Hiele Geometry Test. Hasil penelitian hubungan antara tahapan tingkat berpikir geometri dan indikator kemampuan penalaran matematis dua siswa tingkat 1 visualisasi memenuhi tiga indikator; dua siswa tingkat 2 analisis memenuhi tiga indikator; dan dua siswa tingkat 3 abstraksi deduksi informal memenuhi lima indikator. Kemampuan penalaran matematis rata – rata dari lima indikator hanya pada memberikan alasan terhadap beberapa solusi dan belum dapat memeriksa kesahihan suatu argumen dan menarik kesimpulan yang tepat.